Improving behavioral support for smoking cessation in pregnancy: what are the barriers to stopping and which behavior change techniques can influence these?: application of theoretical domains framework - Campbell, Katarzyna; Fergie, Libby; Coleman-Haynes, Tom; Cooper, Sue; Lorencatto, Fabiana; Ussher, Michael; Dyas, Jane; Coleman, Tim (MDPI, 2018)
Behavioral support interventions are used to help pregnant smokers stop; however, of those tested, few are proven effective. Systematic research developing effective pregnancy-specific behavior change techniques (BCTs) is ongoing. This paper reports contributory work identifying potentially-effective BCTs relative to known important barriers and facilitators (B&Fs) to smoking cessation in pregnancy; to detect priority areas for BCTs development. A Nominal Group Technique with cessation experts (n = 12) elicited an expert consensus on B&Fs most influencing women’s smoking cessation and those most modifiable through behavioral support. Effective cessation interventions in randomized trials from a recent Cochrane review were coded into component BCTs using existing taxonomies. B&Fs were categorized using Theoretical Domains Framework (TDF) domains. Matrices, mapping BCT taxonomies against TDF domains, were consulted to investigate the extent to which BCTs in existing interventions target key B&Fs. Experts ranked “smoking a social norm” and “quitting not a priority” as most important barriers and “desire to protect baby” an important facilitator to quitting. From 14 trials, 23 potentially-effective BCTs were identified (e.g., information about consequences). Most B&Fs fell into “Social Influences”, “Knowledge”, “Emotions” and “Intentions” TDF domains; few potentially-effective BCTs mapped onto every TDF domain. B&Fs identified by experts as important to cessation, are not sufficiently targeted by BCT’s currently within interventions for smoking cessation in pregnancy.